SENTIMENT ANALYSIS OF TWITTER DATA ON DISTANCE LEARNING USING NAÏVE BAYES ALGORITHM - Putri Rana Khairina; Desti Fitriati (Kresnamedia Publisher, 2021)
Covid-19 is widespread, resulting in a global pandemic. Distance Learning System (DLS) is considered as a solution but, the reality of the implementation of DLS is not in accordance with the expectations of the community. Many twitter users wrote their opinions on DLS. The tendency of public sentiment can be used as a way to improve the existing education system in Indonesia and can be an input for the government in improving the DLS method that is being implemented. Thus, this study produced a system that can analyze tweet sentiment towards DLS. The tweet was obtained using the Twitter API. The method used is Naïve Bayes for the process of classification of positive, negative and neutral sentiments using 600 data. Then, data sharing is done 80% data training and 20% data testing that will be in the text preprocessing first. The accuracy of sentiment analysis of DLS using Naïve Bayes method using 3-fold Cross Validation produces an average of 93%.